Oxidative stress mediates an increased formation of vascular endothelial growth factor in human hepatocarcinoma cells exposed to erlotinib - Rohr-Udilova, Nataliya (Oncotarget, 2017)
The tyrosine kinase inhibitor erlotinib targets the receptor of epidermal growth factor (EGFR) involved in development of hepatocellular carcinoma (HCC). Although inefficient in established HCC, erlotinib has been recently proposed for HCC chemoprevention. Since Cyp3A4 and Cyp1A2 enzymes metabolize erlotinib in the liver, the insights into the mechanisms of erlotinib effects on liver cells with maintained drug metabolizing activity are needed. We applied erlotinib to both commercially available (SNU398, Huh7) and established in Austria HCC cell lines (HCC-1.2, HCC-3). Cyp3A4 and Cyp1A2, microarray gene expression, cell viability, LDH release, DHFC fluorescence were assessed. VEGF expression was analysed by real-time RT-PCR and ELISA. Higher cumulative expression of erlotinib metabolizing enzymes was observed in HCC-1.2 and HCC-3 cells. Gene expression microarray analysis showed upregulation of VEGF signalling by erlotinib. VEGF was increased up to 134 ± 14% (n = 5, p = 0.002) in HCC-1.2, HCC-3 and Huh7 cells. Interventions by Cyp1A2 and Mek2siRNA, MEK inhibitor UO126, diphenylene iodonium, as well as a combination of N-acetylcysteine with selenium all inhibited VEGF upregulation caused by erlotinib. Thus, erlotinib increases VEGF production by mechanisms involving Cyp1A2, oxidative stress and MEK1/2. VEGF may favour angiogenesis and growth of early HCC tumours limiting the therapeutic and chemopreventive effects of erlotinib.